SIRT6 Regulates Osteogenic Differentiation of Rat Bone Marrow Mesenchymal Stem Cells Partially via Suppressing the Nuclear Factor‐κB Signaling Pathway. (17th June 2014) - Sun, Hualing; Wu, Yanru; Fu, Dongjie; Liu, Yinchen; Huang, Cui
Abstract : Sirtuin 6 (SIRT6) is a NAD‐dependent deacetylase involved in lifespan regulation. To evaluate the effect of SIRT6 on osteogenesis, rat bone marrow mesenchymal stem cells (rBMSCs) with enhanced or reduced SIRT6 function were developed. We observed that SIRT6 knockdown significantly reduced the mRNA levels of several key osteogenic markers in vitro, including alkaline phosphatase (ALP), Runt‐related transcription factor 2 (RUNX2), and osteocalcin, while overexpression of SIRT6 enhanced their expression. Additionally, SIRT6 knockdown activated nuclear factor‐κB (NF‐κB) transcriptional activity and upregulated the expression of acetyl‐NF‐κB p65 (Lys310). The decreased osteogenic differentiation ability of rBMSCs could be partially rescued by the addition of NF‐κB inhibitor BAY 11–7082. Furthermore, SIRT6 overexpression in rBMSCs combined with the use of collagen/chitosan/hydroxyapatite scaffold could significantly boost new bone formation in rat cranial critical‐sized defects, as determined by microcomputed tomography and histological examination. These data confirm that SIRT6 is mainly located in the nuclei of rBMSCs and plays an essential role in their normal osteogenic differentiation, partly by suppressing NF‐κB signaling. Stem Cells 2014;32:1943–1955